PENAMBAHAN PROBIOTIK (PROBIO FM) PADA PAKAN MANDIRI BERBAHAN BAKU LOKAL UNTUK KEGIATAN BUDIDAYA IKAN - Endang Bidayani; Ramdhan Aditya; Muhammad Mighfar; Bayu Bayu; Sudirman Adibrata; Yeyen Mardyani (Jurnal Abdi Insani, 2023)
Probiotics (Probio FM) is a liquid probiotic containing several species of lactic acid bacteria which are the result of microbial isolation taken from the digestive tract of Kerinci ducks. The function of probiotics is to maintain the balance of microflora in the intestine by reducing the number of pathogenic microbes in the intestine. The use of Probio FM can increase livestock productivity, namely increasing weight, appetite, and reducing production costs. The entrepreneurial goal of Merdeka Learning Merdeka Campus (MBKM) is the addition of probiotics (Probio FM) to independent pellets to improve the growth performance of cultured fish. The method of activity is the active participation of MBKM students in the independent feed production process with the addition of Probio FM. As a result of the activity, the addition of Probio FM was effective in increasing the growth performance of aquacultured fish. Students get a learning experience in the form of independent feed production skills, and knowledge related to Probio FM.